Tales from a Not-So-Glam TV Star. - Russell, Rachel Renee; Russell, Erin.; Russell, Nikki (New York. Aladdin., 2014)
Nikki's juggling a lot this month. A reality TV crew is following Nikki and her friends as they record their hit song together, plus there are voice lessons, dance practice, and little sister Brianna's latest wacky hijinks. Nikki's sure she can handle everything, but will all the excitement cause new problems for Nikki and Brandon, now that cameras are everywhere Nikki goes?
Donated by Erin McPherson.
710
Accelerated Reader AR
Reading Counts RC
Keywords: Realistic -- Fiction